2008
DOI: 10.1158/1541-7786.mcr-07-2157
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Primary Mammary Tumor Cell Line Reveals that Cyclin D1 Is Regulated by the Type I Insulin-Like Growth Factor Receptor

Abstract: The importance of type I insulin-like growth factor receptor (IGF-IR) overexpression in mammary tumorigenesis was recently shown in two separate transgenic models. One of these models, the MTB-IGFIR transgenics, was generated in our lab to overexpress IGF-IR in mammary epithelial cells in a doxycycline (Dox)-inducible manner. To complement this transgenic model, primary cells that retained Dox-inducible expression of IGF-IR were isolated from a transgenic mammary tumor. This cell line, RM11A, expressed high le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…This supports our earlier findings that short-term doxycycline withdrawal (24-72 h) results not only in the rapid downregulation of the IGF-IR transgene but also leads to reduction in the levels of cyclin D1 and activated Akt (Jones et al, 2008). Thus, the early events of tumor regression after IGF-IR suppression involves downregulation of the cell-cycle regulator cyclin D1 and the loss of the pro-survival effects of Akt leading to reduced proliferation and increased apoptosis of tumor cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This supports our earlier findings that short-term doxycycline withdrawal (24-72 h) results not only in the rapid downregulation of the IGF-IR transgene but also leads to reduction in the levels of cyclin D1 and activated Akt (Jones et al, 2008). Thus, the early events of tumor regression after IGF-IR suppression involves downregulation of the cell-cycle regulator cyclin D1 and the loss of the pro-survival effects of Akt leading to reduced proliferation and increased apoptosis of tumor cells.…”
Section: Discussionsupporting
confidence: 92%
“…Generation of MTB-IGFIR transgenic mice and the primary MTB-IGFIR mammary tumor cell line, RM11A, has been described earlier (Jones et al, 2007(Jones et al, , 2008. To induce transgene expression, standard rodent chow was replaced with rodent chow containing 2 g/kg of doxycycline (Bio-Serv, Frenchtown, NJ, USA).…”
Section: Micementioning
confidence: 99%
“…RJ345 and RJ348 cells were generated in our lab and have previously been described [30]. RJ345 and RJ348 cells were cultured in DMEM containing 10% FBS, 1 mmol/L sodium pyruvate, 10 mmol/L HEPES, 4 mmol/L glutamine, 2 mmol/L hydrocortisone, 5 μg/mL estrogen, 5 μg/mL prolactin, 10 μg/mL epidermal growth factor, 10 μg/mL insulin and 1% antibiotic/antimycotic.…”
Section: Methodsmentioning
confidence: 99%
“…This mechanism of action is exerted by pp60 src [57], c-myb [58,59] and hepatitis B virus X oncogenes [60]. Jones et al suggested that in transformed cells overexpressing IGF-1R, the latter’s proliferative/survival signaling can be ligand-independent above a certain expression level, whereas in normal cells in which the receptor is under expressed, IGF stimulation triggers a robust response [61]. Such ligand-independent/dependent signaling may play an instrumental role when IGF-1 is used at supraphysiological doses as a performance-enhancing drug [15,62,63].…”
Section: The Igf Systemmentioning
confidence: 99%